Characteristics of Patients with Type 2 Diabetes Mellitus (Indian Journal of Public Health Research & Development, 2021)
Diabetes Mellitus (DM) is one of the non-communicable diseases that has the most prevalence of diseasesglobally. This study aimed to determine the characteristics of patients type 2 diabetes mellitus (T2DM) inregional hospital, East Jakarta. The study’s characteristics were age, sex, education, occupation, Body MassIndex (BMI), history of diabetes mellitus, history of hypertension, and blood pressure. The study designuses descriptive studies. The study population was all people with diabetes mellitus in regional hospital, EastJakarta. This study sample was people with type 2 diabetes mellitus in January to March 2019 in the regionalhospital, 170 patients. The sampling technique is by using non-random sampling. The results showed thatpeople with type 2 diabetes mellitus aged over 45 years 86%, male sex 52%, higher education 78.82%,not working 55%, normal BMI 48%, had a history of DM 54%, have a history of hypertension 57%, andnormal blood pressure 65%. The study population’s conclusions were all people with diabetes mellitus in theregional hospital, East Jakarta, aged over 45 years, male sex, higher education, not working, normal BMI,had a history of DM, have a history of hypertension, and normal blood pressure.
Keywords: Type 2 Diabetes Mellitus, characteristics of T2DM, East Jakarta.